User tracking mechanisms and counter measures - Asra ISHTIAQ; Salma Hussain ABBASI; Muhammad ALEEM; Muhammad Arshad Islam Islam (International Journal of Applied Methods in Electronics and Computers, 2017)
Online customers have lots of alternatives while making purchase or discovering information on websites. Now a day, tracking services and passive traffic check are widely used to collect knowledge about user’s internet activities and interests. For end users such tracking has significant privacy implications. So, Privacy becomes a sensitive issue which attracts a lot of user’s attention. Discrimination is a way to differentiate, isolate, or make a difference. User discrimination is a tactic used to present personalized content to the user, based on user profile. It helps the web owner to improve the content of web site. It also ensures that the content caters to largest population of user visiting their website. Our major contribution in this paper is to empirically show the tracking mechanism used for user discrimination on the Web, and also provide defense mechanism against these tracking mechanisms.